Moodle Lesson of the Anatomy and Histology of the Human Placenta [Lección Moodle de Anatomía E Histología de la Placenta Humana] - Osses-Mc Intyre, M; Godoy-Guzman, C (Universidad de la Frontera, 2019)
SUMMARY: The lack of existing human biological samples, mainly due to the ethical-moral restrictions related to obtaining these, highlights the need to search for other teaching and learning alternatives in morphological science. In this sense, the implementation of lessons by means of the MOODLE platform provides the students with the opportunity to interact in a setting that simulates a learning situation that belongs to traditional laboratories. The purpose of this work was to generate a MOODLE lesson on the anatomy and histology of the human placenta, as a complement of the traditional theoretical classroom for students of Obstetrics. To that end, TIC information, images, and resources were sought in libraries and in the Internet, and at the same time a set of histological photographs of placenta samples was made, as well as a video recording of a placental delivery. Later, the coordination and set up of activities was made in the MOODLE platform with a constructivist approach. Furthermore, a satisfaction survey was prepared which was validated by three experts. The total sample consisted of 137 students in the 2th year of obstetrics. A virtual MOODLE laboratory of the anatomy and histology of the human placenta was made, which is constituted by multiple activities with a clinical orientation that allow self-evaluation. The virtual laboratory has helped overcome the lack of human samples, and results of the satisfaction survey applied to the students indicate a positive evaluation of this initiative. © 2019, Universidad de la Frontera. All rights reserved.
Keywords: MOODLE; Human placenta; Histology; Anatomy